Two Decades of Market Abuse in Poland. Market Manipulation, Insider Trading and Unlawful Disclosure of Inside Information from 2002 to 2022 - Martysz, Czesław Bartłomiej; Skrodzka, Joanna (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis. The purpose of the article is to present key conclusions from the analysis of case law, including the most common modus operandi of perpetrators and the characteristic features of the crimes of manipulation, insider trading and unlawful disclosure of inside information. These offenses (classified under the MAR Regulation as market abuse) are particularly harmful to the Polish capital market, as they damage investor confidence in the market and destroy its efficiency. Methodology. The authors, based on the literature, reports of the supervisory authority over the Polish capital market (KPWiG / KNF) and court judgments, have created the first comprehensive study of case law for market abuse in the Polish literature. Results of the research. The duration of the prosecutorial and judicial process for market abuse took 6.5–7.8 times longer than the average criminal trial. The effectiveness of insider trading djudication was significantly lower than in the case of manipulation (46%). The typical modus operandi of manipulation was artificial one-person trading “with oneself” or closely related activity of several people (wash trade). The perpetrators of the market abuses were mostly people with extensive knowledge about how stock exchange works, who tried to hide behind ignorance or speculation during the proceedings, but often market participants were unaware of the illegality of their actions.